Helicobacter pylori eradication induce platelet recovery in idiopathic thrombocytopenic purpura - G. Emilia; G. Longo; M. Luppi; G. Gandini; M. Morselli; L. Ferrara; S. Amarri; K. Cagossi; G. Torelli (PAGEPress Publications, 2001)
Recent reports have suggested an association between Helicobacter pylori infection and idiopathic thrombocytopenic purpura (1TP). The prevalence of H pylori infection and the effect of its eradication in a series of 30 ITP patients were investigated. H pylori infection has been documented in 13 patients (43.33%) by 13C urea breath test and confirmed by histologic examination. Bacterium eradication with antibiotics, obtained in 12 of 13 infected patients (92.3%), led to a complete response in 4 (33.33%) and to a partial response (platelets 90 x IO^L-120 x IO'VL) in 2 (16.66%). The response was maintained for a median of 8.33 months, but 1 patient relapsed 7 months after eradication. Search for H pylori infection seems appropriate in ITP patients at diagnosis. Bacterium eradication provides a new good option for a non immunosuppressive treatment in some ITP patients. (Blood 2001; 97: 812-814)